2023
DOI: 10.3389/frhs.2023.1112936
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating facilitators to facilitate—Some general comments on a strategy for knowledge implementation in health services

Abstract: Numerous endeavours to ensure that day-to-day healthcare is both evidence-based and person-centred have generated extensive, although partial, comprehension of what guarantees quality improvement. To address quality issues, researchers and clinicians have developed several strategies as well as implementation theories, models, and frameworks. However, more progress is needed regarding how to facilitate guideline and policy implementation that guarantees effective changes take place in a timely and safe manner.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Given the complexity of capturing the mechanisms by which implementation support produces implementation outcomes, further investigations are needed into ISPs' collaboration with recipients of implementation support. Specifically, more implementation studies are needed on how ISPs make choices about the strategies and approaches they use based on recipients' attitudes towards implementation support and other contextual factors of the implementation setting ( 11 , 12 ). Previous research has demonstrated that ISPs spend as much time brokering connections, addressing power differentials, and building relationships as they do on more technical work such as conducting improvement cycles ( 2 ), suggesting that ISPs view the quality and mutuality of their relationships with recipients of implementation support as critical for implementation success.…”
Section: Introductionmentioning
confidence: 99%
“…Given the complexity of capturing the mechanisms by which implementation support produces implementation outcomes, further investigations are needed into ISPs' collaboration with recipients of implementation support. Specifically, more implementation studies are needed on how ISPs make choices about the strategies and approaches they use based on recipients' attitudes towards implementation support and other contextual factors of the implementation setting ( 11 , 12 ). Previous research has demonstrated that ISPs spend as much time brokering connections, addressing power differentials, and building relationships as they do on more technical work such as conducting improvement cycles ( 2 ), suggesting that ISPs view the quality and mutuality of their relationships with recipients of implementation support as critical for implementation success.…”
Section: Introductionmentioning
confidence: 99%